MENGOPTIMALKAN PERTANIAN BERKELANJUTAN: PROGRAM PELATIHAN PEMBUATAN ECO-ENZYME DAN POC UNTUK PENINGKATAN PRODUKTIVITAS TANAMAN DAN KESEHATAN LINGKUNGAN - Bakri, Muliati; Aprilla, St. Mutia; Tamrin, Hasliana; Bahar, Noviani; Said, Muh. Rafly; Zahra, St. Fatimatuz; Salsabila, Nabila (Jurnal Abdi Negeriku, 2024)
Real Work Lectures (KKN) is a program that aims to apply science and technology in the context of community service. This service was carried out in Allepolea Village, Bontokapetta 2 Ward, which is an area located in Lau District, Maros Regency, South Sulawesi Province, Indonesia. Sustainable agriculture is the main focus in efforts to increase plant productivity and maintain environmental balance. One of the proposed approaches is through a training program for making eco-enzymes and POC (Liquid Organic Fertilizer) as an environmentally friendly solution. This program aims to optimize agriculture by increasing plant productivity and maintaining environmental health. Through this training, farmers will be equipped with knowledge and skills in producing eco-enzymes and POC effectively. It is hoped that the application of this technology can have a positive impact on agricultural results and at the same time minimize negative impacts on the environment. This study supports the vision of sustainable agriculture through innovative approaches to natural resource management.